Micro price heterogeneity and optimal inflation - Sergio Santoro; Henning Weber (European Central Bank (ECB), 2023)
This paper discusses the normative implications of the micro evidence on heterogeneity in price setting gathered by the Price-setting Microdata Analysis Network (PRISMA) for the level of inflation that central banks should target. The micro price data underlying the consumer price index are used to estimate relative price trends over the product life cycle. Minimising the welfare consequences of relative price distortions in the presence of these trends requires targeting a significantly positive inflation rate in France, Germany and Italy: the steady-state inflation rate, jointly maximising welfare in all three countries, ranges from 1.1% to 1.7%. Other considerations not taken into account in the present paper may push up optimal inflation targets further. The welfare costs of targeting an inflation rate of zero, as suggested by monetary models ignoring relative price trends, or of targeting 4%, turn out to be substantial.
Keywords: E31; E52; 330; optimal inflation target; relative price trends; welfare